Hidrelétricas e (re)ordenamento do território: uma comparação entre os povos amazônicos (Brasil) e das montanhas da Catalunya (Espanha) - Maria Madalena Aguiar Cavalcante; Antoni Francesc Tulla Pujol (Confins)
The use of rivers for energy generation through hydroelectric power plants causes different impacts, both ecological, economic and social. Among them, the (de) territorialisation of populations in the surroundings of reservoir, this constitutes one of the most conflicting process, since the displacement is compulsory, and the resettlement process does not necessarily present the restitution of daily activities, causing a (re) ordering in their territories. In this sense, the objective of the article is to compare two (de) territorialized settlements by hydroelectric power plants: one in the Amazon/Brazil, called Teotonio, and the other in Catalunya/Spain, called Tiurana, in order to demonstrate the main difficulties in the (re) territorialization process. For the methodological development was considered settlements that had similarities, such as: characteristics of traditional peoples that were totally affected by the reservoir of hydroelectric plants and have been resettled. The data were collected through semi-structured questionnaires to obtain comparative information between the activities carried out in the old settlement and in the present one. The results show that more than 90% of those interviewed in Teotonio/Brazil and 65% in Tiurana/Spain presented difficulties in reestablishing their economic activities, even, no longer fulfilling them. The conclusion is that in both cases, the use of the river has been to meet the needs of large industrial centers, while the settlements affected by the reservoir, upon being resettled, do not have the reestablishment of their essential activities guaranteed, resulting in the emptying of the new place, making it just a memorial.